The Role of Environmental Economy in The Economic System of The Country - Boymurodov Behzod; Akbarova Laila Upashevna (Open Academia, 2023)
This article provides an overview of the field of environmental economics and its relationship with environmental science, some contemporary problems of environmental economics and issues affecting them
Keywords: environment; economy; climate; natural resources